Teachers’ perceptions of the barriers to STEM teaching in Qatar’s secondary schools: a structural equation modeling analysis - Sellami, Abdellatif; Santhosh, Malavika; Bhadra, Jolly; Ahmad, Zubair (Frontiers in Education, 2024)
Indeed, educators form the bedrock of educational excellence and wield a significant influence on students' academic achievements. More specifically, the instructional techniques employed by teachers and their adept utilization in the classroom are key factors in determining whether students choose to pursue or persist in STEM (science, technology, engineering, and mathematics) fields of study and careers. This research sought to delve into the barriers that high school STEM teachers encounter in teaching STEM. Data for this research was collected using a survey that involved 290 secondary high school (11th and 12th grade) STEM teachers from thirtynine schools. Structural equation modeling (SEM) was employed to investigate teachers' perceived barriers that hinder effective STEM instruction. The research findings revealed the significance of school-related, student-related, technology-related, and teaching-related barriers to teaching STEM. The study's findings offer essential evidence that can inform educational policy and guide the development of effective STEM learning practices in Qatar's high schools.